Noteworthy records of corticioid fungi from Ichnia National Nature Park - Shevchenko, M.V. (Український ботанічний журнал, 2018)
Corticioid fungi constitute a heterogeneous group in terms of origin; they belong to various orders of Agaricomycetes (Basidiomycota). According to the available data, ca 280 species of this group have been so far recorded in Ukraine. As compared to other countries of Europe, diversity of corticioid fungi in Ukraine has been insufficiently studied. We made observations and collected corticioid fungi in June–October, 2016 and in March–October, 2017 in forests and woods of Ichnia National Nature Park (Ichnia District, Chernihiv Region, Ukraine). Upon identification of the herbarium specimens collected over the study area, we recorded 90 species of corticioid fungi. This article reports three noteworthy records of corticioid fungi. Two species, Amylocorticium canadense and Tubulicrinis glebulosus, are new records for Ukraine; another one, Aleurodiscus dextrinoideocerussatus, is a rare species both in Ukraine and globally, collected in our country for the second time, and a new record for the Forest-Steppe zone. The specimens were examined in 5% aqueous potassium hydroxide solution, Melzer's reagent and Lactophenol cotton blue. For all the species, we provide descriptions of the examined specimens, along with the original photos, substrate specialization and global distribution details. The collected specimens are deposited in the Mycological Herbarium of the M.G. Kholodny Institute of Botany, National Academy of Sciences of Ukraine (KW-M). Кортиціоїдні гриби належать до різних порядків класу Agaricomycetes (Basidiomycota) і складають гетерогенну за походженням групу грибів. В Україні, за сучасними даними, відомо близько 280 видів грибів цієї групи. У порівнянні з іншими країнами Європи, видове різноманіття кортиціоїдних грибів України досліджено значно гірше. Матеріалами для цієї статті були зразки, зібрані протягом червня–жовтня 2016 р. та березня–жовтня 2017 р. у лісових угрупованнях Ічнянського національного природного парку (Ічнянський р-н, Чернігівська обл., Україна). На основі аналізу власних гербарних матеріалів в районі дослідження нами було виявлено 90 видів кортиціоїдних грибів. У статті наведені дані про цікаві знахідки трьох видів грибів. Два із них (Amylocorticium canadense та Tubulicrinis glebulosus) – нові для України, один (Aleurodiscus dextrinoideocerussatus) є рідкісним як в Україні, так і у світі, вдруге виявлений на території країни і є новим для Лісостепової зони. Для дослідження мікроструктур виготовляли тимчасові мікропрепарати у 5%-му водному розчині гідроксиду калію, реактиві Мельцера та бавовняному синьому у молочній кислоті. Для всіх видів подані описи досліджених зразків, що супроводжуються оригінальними фотографіями, інформацією про субстратну спеціалізацію та про поширення у світі. Зібрані зразки передано до Національного гербарію Інституту ботаніки ім. М.Г. Холодного НАН України (KW-М). Кортициоидные грибы принадлежат к разным порядкам класса Agaricomycetes (Basidiomycota) и составляют гетерогенную по происхождению группу грибов. В Украине, по современным данным, известно около 280 видов грибов этой группы. В сравнении с другими странами Европы, видовое разнообразие кортициоидных грибов Украины исследовано значительно хуже. Материалами для настоящей статьи послужили образцы, собранные в июне–октябре 2016 г. и марте–октябре 2017 г. в лесных сообществах Ичнянского национального природного парка (Ичнянский р-н, Черниговская обл., Украина). На основе анализа собственных гербарных материалов в районе исследования нами было обнаружено 90 видов кортициоидных грибов. В статье приведены данные об интересных находках трех видов грибов. Два из них (Amylocorticium canadense и Tubulicrinis glebulosus) – новые для Украины, один (Aleurodiscus dextrinoideocerussatus) является редким как в Украине, так и в мире, второй раз обнаружен на территории страны и является новым для Лесостепной зоны. Для исследования микроструктур изготавливали временные микропрепараты в 5%-ном водном растворе гидроксида калия, реактиве Мельцера и хлопчатобумажном синем в молочной кислоте. Для всех видов представлены описания исследованных образцов, сопровождающиеся оригинальными фотографиями, информацией о субстратной специализации и о распространении в мире. Собранные образцы переданы в Национальный гербарий Института ботаники им. Н.Г. Холодного НАН Украины (KW-М).